War Booty in the Perspective of International Humanitarian Law: A Side Effect of Armed Conflict in Afghanistan - Lia Yulia; Zurria Sakinah; Danial (Universitas Serang Raya, 2024)
War booty is a valuable object including military equipment taken forcibly from the opposing party during the war. The purpose of conducting war booty is to weaken the opposing party. The problem is first; What is the status of means of war as war booty in armed conflict based on the 1907 Hague Convention? Second; What are the side effects of the Taliban's actions in seizing American weapons after the armed conflict in Afghanistan? The method used is normative juridical, with a legal principles approach. While the data analysis is qualitative juridical analysis, which analyzes problem identification based on secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. The results of this study are: First, the status of means of war as spoils of war in armed conflict based on the 1907 Hague Convention on Means of War as spoils of war which as long as the spoils are movable objects belonging to the state that can be used for military operations and not civilian objects then the spoils are the property of the military authorities occupying the area of conflict before there is a peace agreement from the warring parties; Second, that the side effect of the spoils of war by the Taliban against military vehicles, helicopters, drones, weapons and night goggles is compensation, while against objects that still exist must be returned in the event of a peace agreement, this is regulated in Article 53 of the Hague Convention 1907 Jo Article 54 paragraph 2 and 4 Additional Protocol 1 of 1977.